2004
DOI: 10.3732/ajb.91.10.1523
|View full text |Cite
|
Sign up to set email alerts
|

Dinoflagellates: a remarkable evolutionary experiment

Abstract: In this paper, we focus on dinoflagellate ecology, toxin production, fossil record, and a molecular phylogenetic analysis of hosts and plastids. Of ecological interest are the swimming and feeding behavior, bioluminescence, and symbioses of dinoflagellates with corals. The many varieties of dinoflagellate toxins, their biological effects, and current knowledge of their origin are discussed. Knowledge of dinoflagellate evolution is aided by a rich fossil record that can be used to document their emergence and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
260
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(265 citation statements)
references
References 121 publications
1
260
2
2
Order By: Relevance
“…Hatena arenicola (Katablepharidophyta) bears a close evolutionary relationship with cryptophytes, in which permanent chloroplasts are established (25). A similar situation has been observed in Dinoflagellata (26) and Cercozoa (27), in which certain species have established the division synchronization, whereas others still have a transient endosymbiotic relationship with photosynthetic eukaryotes or cyanobacteria. The above observations suggest that division synchronization was necessary for the establishment of permanent chloroplasts (13).…”
Section: Discussion Evolutionary Linkage Between Cytokinesis and Chlomentioning
confidence: 73%
“…Hatena arenicola (Katablepharidophyta) bears a close evolutionary relationship with cryptophytes, in which permanent chloroplasts are established (25). A similar situation has been observed in Dinoflagellata (26) and Cercozoa (27), in which certain species have established the division synchronization, whereas others still have a transient endosymbiotic relationship with photosynthetic eukaryotes or cyanobacteria. The above observations suggest that division synchronization was necessary for the establishment of permanent chloroplasts (13).…”
Section: Discussion Evolutionary Linkage Between Cytokinesis and Chlomentioning
confidence: 73%
“…Dinoflagellates are characterized by a very large genome (Hackett et al, 2004) and a number of unique features such as DNA containing 5-hydoxymethylmuracil (Rae, 1976), a lack of the usual histones (Rizzo, 1981) and transcriptional regulatory elements (Li and Hastings, 1998). Dinoflagellates contain a conserved spliced leader sequence (Zhang et al, 2007), and highly expressed genes with elevated copy numbers and tandem repeats (Bachvaroff and Place, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dinoflagellates are differentiated from one another by the pattern of thecate or amphiesma which is made up of cellulose plates that protect the cells from the tugor pressure [1,3]. Previous study on the fossils of ancient dinoflagellates revealed six patterns of plate that classified the species into different major groups; gymnodinoid, suessioid, peridinioid, gonyaulacoid, dinophysoid, and prorocentroid [4].…”
Section: Dinoflagellates: Multifaceted Microorganismsmentioning
confidence: 99%
“…Photosynthetic products are important for the continuum of coral metabolism, growth, reproduction and survival [10,16,17]. This is because oxygen-byproduct of dinoflagellates fuels up the rate of calcification by the reef-building corals [1,10]. In return, the reefs provide protection for zooxanthelle against grazers and free access of nutrients in the nutrient-poor environment [16].…”
Section: Ecological Importancementioning
confidence: 99%
See 1 more Smart Citation